The potential of electronic nose technology in lung transplantation: a proof of principle. Issue 3 (11th July 2022) - Wijbenga, Nynke; Hoek, Rogier A.S.; Mathot, Bas J.; Seghers, Leonard; Aerts, Joachim G.J.V.; Manintveld, Olivier C.; Hellemons, Merel E.
With each exhaled breath, thousands of molecules are expelled. Every person has a unique composition of this expelled air, the so-called breathprint, representing their current state of health. Identification of individual volatile organic compounds (VOCs), although specific, is an extremely time-consuming process and hard to implement in routine clinical care. An electronic nose (eNose) can be used to capture the complete mixture of VOCs in exhaled air by several cross-reactive gas sensors. Without identifying individual components in expelled air, the sensor captures information that results in a breathprint pattern which can be analysed with artificial intelligence using pattern recognition [1, 2]. Consequently, using an eNose to collect real-time measurements of the breathprint has potential as a cheap and fast point-of-care tool in clinical practice. In recent years, exhaled breath analysis using eNose technology has gained increasing attention and has demonstrated great potential as a real-time noninvasive diagnostic tool, where different vendors are available [3]. For example, promising results were demonstrated in diagnosis of asthma phenotypes and interstitial lung diseases, with international confirmation studies ongoing to bring this technology to outpatient clinics [3–5]. Exhaled breath analysis using eNose technology holds promise as a point-of-care indicator of clinical status after lung transplantation. This case study invites further exploration of eNose technology in the field of lung transplantation. https://bit.ly/3wgQ3DE